KEDUDUKAN ANAK ANGKAT DALAM PEMBAGIAN HARTA WARIS MENURUT PERSPEKTIF HUKUM ADAT BALI - I Wayan Wahyu Wira Udytama; Yogi Yasa Wedha; Ni Nyoman Ayu Tri Sukmarini (Faculty of Law, Mahasaraswati University, Denpasar, 2024)
In Indonesia, the phenomenon of child adoption is very common even though in each traditional region, there are various different procedures and systems. In some cases, adopted children completely sever their relationship with their biological parents, and in other cases there are also those who retain the right to continue their relationship with their biological parents. The definition of an adopted child in Bali is someone else's child who someone takes, cares for and treats as their own offspring. In its development, adoption of children in Bali is no longer in accordance with existing regulations, especially the conditions for children being adopted. The adoption of a child will also result in inheritance for the adopted child himself. This development certainly raises its own problems, both regarding the adoption of children and their inheritance. So based on the description above, the aim of this research is to examine the traditional procedures for adopting children according to the Balinese Customary Law Perspective as well as the position of adopted children regarding their parents' inheritance